The ‘Umka’ landslide - Uroš Đurić; Dragana Đurić; Miloš Marjanović; Biljana Abolmasov; Ivana Vasiljević (Journal of Maps)
We present an in-depth landslide map of the ‘Umka’ landslide near Belgrade, Serbia, at a scale of 1:5000. The map delineates elements at risk, primarily buildings and road infrastructure impacted by the landslide displacements of several cm per year, introduced during frequent reactivation stages. The Main map results from a survey of over 350 buildings and more than 7 km of state and local roads. The acquisition techniques included engineering geological field mapping, building survey, and visual interpretation of high-resolution UAV images. This is the first case of an integrated approach to mapping elements at risk within an urbanized active landslide in Serbia. Presently, over 490 people continue to reside at the site, facing daily landslide risks. This research and map hold substantial value for local authorities and decision-makers, providing a basis for conducting landslide risk analyses and implementing effective risk mitigation strategies or remedial measures.